O‘ZBEK VA QORAQALPOQ TILLARIDAGI “NUTQ” MA’NOLI FRAZEMALARDA PARADIGMATIK VA SINTAGMATIK MUNOSABATLAR - Allambergenova, N.G. (SCIENCE and SOCIETY, 2022)
The article is analyzed paradigmatic and syntagmatic relations in the phrase "speech" in the Uzbek and Karakalpak languages. Phrases have a specific paradigm and syntactic function to connect with other parts of speech.